2021
DOI: 10.1080/20469047.2021.1967625
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome in neonates with hypoxic-ischaemic encephalopathy managed with therapeutic hypothermia in a tertiary-level public hospital outside an intensive care unit setting

Abstract: Background: Management of hypoxic-ischaemic encephalopathy (HIE) by therapeutic hypothermia (TH) is a major challenge in low-and middle-income countries (LMIC) because of the limited resources. Clinicians in LMIC offer this intervention outside neonatal intensive care units (NICU). The effect of this practice on neurodevelopmental outcome is not well known. Aim: To determine neurodevelopmental outcome in neonates with HIE managed with TH outside NICU settings. Methods: : This was a retrospective descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In a separate study in our setting, we reported an abnormal outcome in 32% of neonates who were cooled when assessed at 18-24 months. (15) Another study from South Africa reported severe neurodevelopmental outcomes in 18% of infants assessed at 1 year of age. (20) Limitation of this retrospective observational study include the fact that there was incomplete information especially on the reasons for not cooling neonates who were considered to have moderate-tosevere encephalopathy and were not cooled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a separate study in our setting, we reported an abnormal outcome in 32% of neonates who were cooled when assessed at 18-24 months. (15) Another study from South Africa reported severe neurodevelopmental outcomes in 18% of infants assessed at 1 year of age. (20) Limitation of this retrospective observational study include the fact that there was incomplete information especially on the reasons for not cooling neonates who were considered to have moderate-tosevere encephalopathy and were not cooled.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a multicenter randomized clinical trial (HELIX trial) from LMICs reported that TH was associated with increased mortality, resulting in authors of this paper calling for an immediate cessation of cooling in LMICs (12). TH continues to be used as an intervention to reduce the incidence of abnormal neurodevelopmental outcomes in neonates with intrapartum asphyxia in many centers in LMIC (13)(14)(15)(16). With concerns raised by the HELIX trial, it is important that continued use of TH in LMIC be monitored with a special focus on mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this current study reports short-term outcomes of neonates who were cooled but it is important that long-term outcomes be assessed so that the relative low mortality rate at hospital discharge is not outweighed by high mortality post-discharge and increased risk for abnormal neurodevelopmental outcomes. In a separate study in our setting, we reported an abnormal outcome in 32% of neonates who were cooled when assessed at 18–24 months [ 15 ]. Another study from South Africa reported severe neurodevelopmental outcomes in 18% of infants assessed at 1 year of age [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have been offering TH in neonates with HIE in SA for more than a decade, with apparently reasonable outcomes, with in-hospital mortality of 13 -14% [2,5] and normal neurological outcome or mild impairment in 82% at 12 months [2] and 68% at 18 -24 months. [8] We therefore have a major concern with this 'all or none' approach recommended by the HELIX authors. In addition, contrary to what the HELIX authors have recommended, a recent meta-analysis on TH for asphyxiated neonates with encephalopathy recommends that TH should be offered as part of the standard of care, as the reduction in mortality was found to be greatest in LMICs.…”
Section: Editorialmentioning
confidence: 99%